2018
DOI: 10.1249/mss.0000000000001576
|View full text |Cite
|
Sign up to set email alerts
|

Power-to-Strength Ratio Influences Performance Enhancement with Contrast Training

Abstract: The PSR appears to influence the effectiveness of CST, with performance enhancement more likely in those with a lower PSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In addition, for the force-velocity profiling, loaded SJ and loaded CMJ were also performed. To examine the influence of strength level on performance enhancement using resistance priming, subjects were divided into stronger and weaker groups, followed by analyzing the performance outcomes of each group ( 34 ). The procedures for the priming and control conditions are provided in detail in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, for the force-velocity profiling, loaded SJ and loaded CMJ were also performed. To examine the influence of strength level on performance enhancement using resistance priming, subjects were divided into stronger and weaker groups, followed by analyzing the performance outcomes of each group ( 34 ). The procedures for the priming and control conditions are provided in detail in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The strength of the correlation coefficient was determined based on the classifications outlined by Cohen ( 5 ), where r values of 0.10–0.29, 0.30–0.49, and ≥0.5 indicated a small, moderate, and large effect, respectively. After initial analysis of combining subject data and subsequent finding regarding the significantly positive relationship between the individual half squat 1 RM-to-body mass ratio (i.e., relative half squat 1RM) and percentage change in 0% 1RM CMJ height in the priming condition, the median split technique was used to separate subjects into 2 groups ( 9 , 34 ): the stronger group with the highest relative half squat 1RM (1.93–2.67 kg·kg −1 ; n = 10) and the weaker group with the lowest relative half squat 1RM (1.37–1.92 kg·kg −1 ; n = 10). Independent-sample t -tests were used for comparisons between the stronger and weaker groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, within-session performance enhancement with contrast training can be influenced by individual levels of maximal strength (23), power (22), and the power-to-strength ratio (PSR) (22). We previously reported that in subelite Australian Rules Football (ARF) athletes, contrast training (high-load [85% 1RM] half squats followed by low load [30% 1RM] squat jumps) improved within-session performance (squat jump peak power) by approximately 8% but only for individuals with a lower PSR (≤19.1 W·kg −1 ) (22). Whether the individual PSR influences improvements in power-related outcomes after a contrast training intervention has, however, not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to compare the effects of a contrast training protocol, previously shown to enhance within-session performance (22), with resistance training using a progressive, block periodization approach on strength-related and power-related outcomes. A secondary aim was to explore whether the PSR, previously shown to modulate within-session performance enhancement with contrast training (22), influenced the improvements with training. We hypothesized that 1) both contrast training and progressive resistance training would improve several power-related measures, but greater improvements would occur with contrast training, and 2) that greater improvements in power-related measures would occur in those with a lower PSR at baseline.…”
Section: Introductionmentioning
confidence: 99%